Bioactive agents with biomimmetic remineralizing action (Research, Society and Development, 2022)
Dental caries is considered by the WHO to be the second most common disease in the world. Considering that its action is due to enamel demineralization carried out through the metabolism of carbohydrates by dental biofilm bacteria, the use of fluoride toothpastes was established as an effective method of control. Fluoride toothpastes are an integral part of individual care to prevent caries. However, even with its proven effectiveness, there is still a prevalence of the disease. Therefore, different bioactive agents are being studied, looking for an action that is fluoride auxiliary, equivalent or even better. This review aimed to carry out a bibliographic survey of the last five years on the different bioactive agents used in the biomimetic remineralization process of different dental tissues and in the modulation of caries disease, both in vitro and in vivo studies. Different bioactive agents used for enamel remineralization were addressed in this review, including various forms of calcium phosphate as well as self-assembling peptides. Of the 275 studies found, 45 studies met the inclusion criteria and were used for this review. Published studies demonstrate the potential of different bioactive agents in the biomimetic remineralization of enamel. However, further studies are needed to further substantiate existing results and to extend and refine the application of these agents in modern oral hygiene.